Kausalitas Utang Luar Negeri dan Pertumbuhan Ekonomi di Indonesia: Aplikasi Richardian Equivalence Hypothesis - Birgitta Dian Saraswati; Gabriella Gabriella (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This study aims to identify the causal relationship between foreign debt and economic growth and to identify the direction and influence between foreign debt and economic growth in Indonesia, both in the short term and in the long term. By using the Granger causality test method and the estimation of the error correction model with a time period of 1990-2019, this study shows that there is a one-way causality relationship between foreign debt and economic growth in Indonesia. Foreign debt affects economic growth both in the short term and in the long term. This proves that the Richardian Equivalence Hypothesis which states that foreign debt has no effect on economic growth has not been proven to occur in Indonesia.